2018
DOI: 10.2174/1389557518666180423112154
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Dipeptidyl Peptidase IV: A Therapeutic Target for Diabetes and Cancer

Abstract: Dipeptidyl Peptidase is one of the novel targets for antidiabetic and anticancer drugs. The dipeptidyl amminopeptidase IV, expressed in mammalian, releases X-Pro/Ala dipeptides from the N-terminus of peptides. It is responsible for the degradation of the incretin hormones which regulate blood glucose level. At present several DPP-IV inhibitors are approved for type-2 diabetes mellitus. These enzymes are also expressed in dimeric form on the surface of different cells (mature thymocytes, activated T cells, B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 51 publications
0
27
0
1
Order By: Relevance
“…In fact, the roles of DPP-4 in tumorigenesis and progression, respectively, have been reviewed recently. 144,145 In lung cancer and pancreatic cancer, DPP-4 inhibitor can assuredly reduce cancer progression and promote the overall survival. 146 However, in breast cancer, prostate cancer, and endometrial carcinoma, DPP-4 inhibition would cause the opposite consequence which promotes cancer progression.…”
Section: Caution Of Using Dpp-4 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the roles of DPP-4 in tumorigenesis and progression, respectively, have been reviewed recently. 144,145 In lung cancer and pancreatic cancer, DPP-4 inhibitor can assuredly reduce cancer progression and promote the overall survival. 146 However, in breast cancer, prostate cancer, and endometrial carcinoma, DPP-4 inhibition would cause the opposite consequence which promotes cancer progression.…”
Section: Caution Of Using Dpp-4 Inhibitorsmentioning
confidence: 99%
“…67,147,148 The role of DPP-4 inhibition in cancer treatment is inconclusive, but it is certain that DPP-4 inhibition in tumorigenesis and tumor development in site-specific tumor should be considered. 144,145 In addition to cancer development, opportunistic infection is another issue of DPP-4 inhibition. Anno et al reported a 69-year-old DM patient, who developed fever after taking vildagliptin for 1 week owing to hypercytokinemia.…”
Section: Caution Of Using Dpp-4 Inhibitorsmentioning
confidence: 99%
“…DPP-IV is expressed in the liver, kidney, adrenal gland, intestine, placenta, spleen, lymphocytes and endothelial cells (Kshirsagar et al, 2011). This enzyme plays an important role in tumour invasion, inflammation regulation, cell migration, immune response, tissue remodelling, signal transduction and cell apoptosis (Yang et al, 2018;Davanso et al, 2019;De et al, 2019). Therefore, the regulation of DPP-IV may play a broad role in human health.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of type II diabetes is based on the use of synthetic oral hypoglycaemic agents, which sometimes produce adverse effects, including hypoglycaemic episodes and death (Camafort‐Babkowski, ). In this regard, researchers are searching for novel and natural drugs with potential inhibitory activity against dipeptidyl peptidase IV (DPP‐IV), a target for antidiabetic and anticancer drugs (Zúñiga‐Guajardo et al ; De et al ). DPP‐IV is a protease that inactivates incretin hormones, that is, glucose‐dependent insulin tropic polypeptide (GIP) and glucagon‐like peptide 1 (GLP‐1).…”
Section: Introductionmentioning
confidence: 99%
“…GIP and GLP‐1 are hormones involved in insulin secretion controlling pancreatic β‐cell proliferation and survival. Inhibition of DPP‐IV prolongs the activity of GIP and GLP‐1 maintaining glucose homeostasis (Green et al, ; De et al ). Currently, different inhibitory DPP‐IV peptides have been isolated from amaranth, wheat, soy, black bean, salmon, milk, whey, zein, lysozyme and porcine skin gelatin (Uchida et al ; Li‐Chan et al ; Velarde‐Salcedo et al ; Nongonierma and FitzGerald, ; De et al ), among others.…”
Section: Introductionmentioning
confidence: 99%